Electrodeposition of iridium oxide by cyclic voltammetry: Application of response surface methodology - Kakooei, S. (EDP Sciences, 2014)
The effects of scan rate, temperature, and number of cycles on the coating thickness of IrOX electrodeposited on a stainless steel substrate by cyclic voltammetry were investigated in a statistical system. The central composite design, combined with response surface methodology, was used to study condition of electrodeposition. All fabricated electrodes were characterized using electrochemical methods. Field emission scanning electron microscopy and energy-dispersive X-ray spectroscopy were performed for IrOX film characterization. Results showed that scan rate significantly affects the thickness of the electrodeposited layer. Also, the number of cycles has a greater effect than temperature on the IrOX thickness. Â© 2014 Owned by the authors, published by EDP Sciences.